Iatrogenesis in the Intensive Care - Oksana I. Kosukhina; Ekaterina S. Kachenkova; Gennadiy N. Germanov; Yuliya V. Zbrueva (Общая реаниматология)
The problem of iatrogenesis in the medical practice is still urgent: according to published data, in healthcare institutions of the Ministry of Public Health of the Russian Federation, about 50.0% of errors in medical care are made by surgeons; among these errors, diagnostic errors prevail (80.0 %) due to improper examination of patients and lack of follow up. Together with surgeons, anesthesiologists and intensivists are in the top five of physicians who demonstrated the greatest number of defects in medical care (about 30.0%).The purpose of our study is prevention of iatrogenesis in the intensive care unit (ICU).Materials and methods. We analyzed findings of the forensic examination and evaluation of medical care of a patient with knife wounds.Results. We determined the immediate cause of death, and describe the causal link between the outcome and identified defects in the medical care.Conclusion. Preventing the iatrogenesis in ICU is right strategy to improvemethe medical care quality.